Da rua para o shopping Feiraguay: desenho urbano e memória visual do comércio popular em Feira de Santana, BA (1970-2012) - Queiroz, Amanda Maracajá Vaz de Lima (2014)
The social productionof a group can be seen from the visual memories of a urban space So, the street vendors group trajectory in Feira deSantana city (Bahia- Brazil), 1970-2012, becomes an important piece of this research, since theformalized trade of goods redesignstheurban contexture and recreates the city. “Feiraguay” -objectof this research- brings topics that are able to identifythe process ofchanging the open market image into a popular shopping mall, resulting in a new group imageandidentity where the street vendors becomemicroand small businessmen. The research analyzes “Feiraguay” urban spacephenomenologically and newenvironmentgenerated by thisurbanandsocialphenomenain the present moment. As amethodological process, the urban designhasthe images like a visual base andmemory resource wich allows a social reality critical view about this group and the comprehension about its visual memory construction based in existential space metamorphosescontributes to Feira deSantana visual culture.